CRIMINAL LAW POLICY OF ILLEGAL PHARMACEUTICAL PREPARATIONS IN THE HEALTH OMNIBUS LAW - Firman Erry Probo; Anis Widyawati; Duhita Driyah Suprapti (RADJA PUBLIKA, 2024)
The purpose of the omnibus law is to simplify the legislation amidst the overlapping legal conditions in Indonesia. The purpose of this article is to explain how the criminal law policy of the Omnibus Law applies to the circulation of illegal pharmaceutical preparations in Indonesia, seen from the position of the criminal article regarding the circulation of pharmaceutical preparations in Law Number 17 of 2023 concerning Health. Where Law Number 17 of 2023 concerning Health has revoked the old Health Law, namely Law Number 36 of 2009 concerning Health. This raises doubts for law enforcement officers in law enforcement efforts, whether they can still use the omnibus law of the Job Creation Law which has changed the article related to Illegal Pharmaceutical Preparations in the old Health Law. Based on the results of research on applicable laws and theories related to the formation of the omnibus law, the author argues in the conclusion that the criminal law policy of pharmaceutical preparations in the Health omnibus law aims to simplify the licensing regulations for pharmaceutical preparations into one Law, namely the Job Creation Law. Laws using the omnibuslaw method can only be repealed by the same law so that the articles in the old Health Law which have been amended in the job creation law are still declared valid and can be used by law enforcement officials in enforcing the law against the distribution of illegal pharmaceutical preparations.